A Review of Genetic Abnormalities in Unicentric and Multicentric Castleman Disease - Alexandra Butzmann; Jyoti Kumar; Kaushik Sridhar; Sumanth Gollapudi; Robert S. Ohgami (Biology, 2021)
Castleman disease (CD) is a rare lymphoproliferative disorder known to represent at least four distinct clinicopathologic subtypes. Large advancements in our clinical and histopathologic description of these diverse diseases have been made, resulting in subtyping based on number of enlarged lymph nodes (unicentric versus multicentric), according to viral infection by human herpes virus 8 (HHV-8) and human immunodeficiency virus (HIV), and with relation to clonal plasma cells (POEMS). In recent years, significant molecular and genetic abnormalities associated with CD have been described. However, we continue to lack a foundational understanding of the biological mechanisms driving this disease process. Here, we review all cases of CD with molecular abnormalities described in the literature to date, and correlate cytogenetic, molecular, and genetic abnormalities with disease subtypes and phenotypes. Our review notes complex karyotypes in subsets of cases, specific mutations in PDGFRB N666S in 10% of unicentric CD (UCD) and NCOA4 L261F in 23% of idiopathic multicentric CD (iMCD) cases. Genes affecting chromatin organization and abnormalities in methylation are seen more commonly in iMCD while abnormalities within the mitogen-activated protein kinase (MAPK) and interleukin signaling pathways are more frequent in UCD. Interestingly, there is a paucity of genetic studies evaluating HHV-8 positive multicentric CD (HHV-8+ MCD) and POEMS-associated CD. Our comprehensive review of genetic and molecular abnormalities in CD identifies subtype-specific and novel pathways which may allow for more targeted treatment options and unique biologic therapies.